Estrategias metodológicas innovadoras para la participación activa de los estudiantes en el proceso enseñanza – aprendizaje de Ciencias Naturales. Año lectivo 2023 – 2024 - Cumbicus Rivera, Cristina Belén (2024)
The application of innovative methodological strategies, in the execution of the teaching- learning process of Natural Sciences, allows students to develop deep understanding and thus improve their academic performance, for this research was proposed as an objective: <<Improve the academic performance of students, through the application of innovative methodological strategies, to awaken their interest to participate in the teaching-learning process of Natural Sciences, in the eighth year of Higher General Basic Education, in the "Adolfo Valarezo" Educative Unit, academic year 2023 - 2024>>. The method used was inductive, since, through direct observation, it was possible to identify that in the eighth year of GBE a considerable group of students have low academic performance; therefore, through bibliographic research, innovative methodological strategies were determined to improve this reality; the approach was qualitative, significant aspects related to the TLP were identified. According to the nature of the information, it corresponds to a Participatory Action Research; since, once the problem was identified, we interacted with the research subjects to enhance their academic performance, through the development of the intervention proposal. On the other hand, according to the temporality, it is transversal, because it is developed in a relatively short period of time that includes from the diagnosis to the discussion. The results obtained through the evaluation and research instruments implemented determined that innovative methodological strategies such as: learning by elaboration, learning by discovery, problem- based learning, active learning, gamification, Flipped Classroom and information management, allow students to actively participate in the development of the TLP. Finally, it is concluded that the implementation of innovative methodological strategies is effective for the improvement of students' academic performance. Key words: meaningful learning, academic performance, academic motivation, constructivism.